Analysis of influenza epidemics during the COVID-19 pandemic using an improved surveillance system (from 2021 to 2024) - Ludmila S. Karpova; Maria Yu. Pelikh; Kirill A. Stolyarov; Ksenia M. Volik; Tatyana P. Stolyarova; Daria M. Danilenko (Журнал микробиологии, эпидемиологии и иммунобиологии)
Aim. Assessing the effectiveness of new baselines and intensity thresholds of epidemics based on rates of incidence and hospitalization with a diagnosis of “influenza” to clarify the timing of epidemics and their spread throughout the Russian Federation against the backdrop of the COVID-19 pandemic (from 2021 to 2024).